2013
DOI: 10.1093/aje/kwt272
|View full text |Cite
|
Sign up to set email alerts
|

Construct Validation of 4 Food-Environment Assessment Methods: Adapting a Multitrait-Multimethod Matrix Approach for Environmental Measures

Abstract: Few studies have assessed the construct validity of measures of neighborhood food environment, which remains a major challenge in accurately assessing food access. In this study, we adapted a psychometric tool to examine the construct validity of 4 such measures for 3 constructs. We used 4 food-environment measures to collect objective data from 422 Ontario, Canada, food stores in 2010. Residents' perceptions of their neighborhood food environment were collected from 2,397 households between 2009 and 2010. Obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…[9][10][11]26 Previous research in a Canadian context has noted that food availability, food quality and food affordability are better predicted at a smaller geographic scale. 27 Fruit juice consumption is positively associated with FV consumption, suggesting that Canadians consuming fruit juice are, on average, eating more fruit and vegetables. However, the relationship between income decile and fruit juice consumption is strengthened when controlling for FV consumption, which signals that, irrespective of intake of FV, fruit juice consumption is higher among those with lower income.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11]26 Previous research in a Canadian context has noted that food availability, food quality and food affordability are better predicted at a smaller geographic scale. 27 Fruit juice consumption is positively associated with FV consumption, suggesting that Canadians consuming fruit juice are, on average, eating more fruit and vegetables. However, the relationship between income decile and fruit juice consumption is strengthened when controlling for FV consumption, which signals that, irrespective of intake of FV, fruit juice consumption is higher among those with lower income.…”
Section: Discussionmentioning
confidence: 99%
“…The NEMS-S [33] and NEMS-R [34] are inventory-type measures of food stores and restaurants, respectively, that score outlets according to the quality, relative affordability, availability, and marketing of foods and beverages that comprise a large proportion of caloric intake at the population level. Data collection methods employed in the current study have been reported in detail elsewhere [42, 43]. Briefly, the Region of Waterloo’s public health inspection database was used to identify food outlets, and systematic direct observation was used to identify additional outlets and remove non-existent food outlets within the three cities from the sampling frame.…”
Section: Study Region and Datamentioning
confidence: 99%
“…There are thousands of food environment features that are measurable, but not all measures are equal in terms of their ability to raise awareness or inform policy priorities. For example, the Nutrition Measures Survey in Stores (NEMS-S), which has been adapted for use in different Canadian contexts, 15 is an inventory-type measure that assesses the availability, quality and affordability of commonly consumed foods and more nutritious versions of those foods. The NEMS-S provides a score in each of three domains related to nutritious food: availability, quality and affordability.…”
mentioning
confidence: 99%